De eros ao abismo: Um estudo do desejo em Felicidade clandestina, de Clarice Lispector - Roefero, Élcio Luís (2006)
In this Master s thesis we seek to read the concept of desire in Clarice Lispector, starting from the study of O primeiro beijo [The first Kiss], Tentação [Temptation], Felicidade clandestina [Clandestine Happiness], Restos do carnaval [The remains of Carnival] e Os desastres de Sofia [Sofia s disasters], which comprise the book of short stories entitled Felicidade clandestina, published in 1971. Each short story chosen for this work points to a different movement of desire and of learning towards the subject construction. Thus, from the desiring state, the character in Clarice Lispector dives into a realm of self-discovery, wandering from joy to frustration essential in the constant search of themselves. While analyzing this corpus, our main theoretical framework was the convergence of Literature and Psychoanalysis, since the line of research that we follow allows for the study of Lispector s characters always torn between the spoken and the non-spoken. In the introduction, we went through several of the readings carried out about desire and its constitution, finding echo in Freud theories as well as in those of his followers besides taking a glance at the philosophical thought as well. In the first chapter, we weaved our theoretical path between Literature and Psychoanalysis. The following chapters were dedicated to the analyses of the chosen short stories, culminating with the study of Os desastres de Sofia a story that anticipates recurring themes found in Lispector s short stories, especially in terms of childhood constitution as a risky space. When we selected to investigate desire in Lispector s fiction, as well as the unfolding elements and frustrations, we noticed that there was a typical organization of the different forms, by which the characters relations, identities and alterities were interwoven. At the same time, one can see a fertile terrain in which the Other s unknown and flourish in confrontation with the self s unknown